2011
DOI: 10.1209/0295-5075/93/47013
|View full text |Cite
|
Sign up to set email alerts
|

An extended Falicov-Kimball model on a triangular lattice

Abstract: The combined effect of frustration and correlation in electrons is a matter of considerable interest lately. In this context a Falicov-Kimball model on a triangular lattice with two localized states, relevant for certain correlated systems, is considered. Making use of the local symmetries of the model, our numerical study reveals a number of orbital ordered ground states, tuned by the small changes in parameters while quantum fluctuations between the localized and extended states produce homogeneous mixed val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…The eigenvalue spectrum of the FKM Hamiltonian is obtained by numerical diagonalization technique on a finite-size triangular lattice with periodic boundary conditions (PBC). In order to calculate the average values of the physical quantities the classical Monte-Carlo simulation algorithm is employed by 'annealing' over a subset of configurations of the 'classical' variables {ω iσ = f † iσ f iσ } [5,6,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…The eigenvalue spectrum of the FKM Hamiltonian is obtained by numerical diagonalization technique on a finite-size triangular lattice with periodic boundary conditions (PBC). In order to calculate the average values of the physical quantities the classical Monte-Carlo simulation algorithm is employed by 'annealing' over a subset of configurations of the 'classical' variables {ω iσ = f † iσ f iσ } [5,6,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…where the a 1g state is localized and fully occupied by one electron and the doubly degenerate e ′ g states are itinerant and half filled by one electron [27]. Here d † iα , d iα are, respectively, the creation and annihilation operators for itinerant e ′ g electrons and f † i , f i are the same for localized a 1g electrons.…”
Section: Gga+u: Magnetic Orbital and Transport Propertiesmentioning
confidence: 99%
“…It is shown that these systems may very well be described by different variants of the Falicov-Kimball model (FKM) [15,16,23,24,25,26,27,11] on the triangular lattice. The FKM (having two kinds of states namely itinerant states and localized states) was originally introduced to study the metal-insulator transition in the rare-earth and transition-metal compounds [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Many numerical and exact calculations are available for the different extensions of spinless FKM on the bipartite and non-bipatatite lattices in the absence of magnetic field and taking into account interactions between itinerant and localized electrons [30,31,23,24,25,26]. These results show many novel phenomenon like charge and orbital ordering and metal-insulator transition as a function of electron correlations and filling of the electrons.…”
Section: Introductionmentioning
confidence: 99%